A novel technique for heart-thymus en bloc transplantation in nonhuman primates - James T. Nawalaniec; Samantha M. Landino; Jane M. O; Cynthia L. Miller; Abbas Dehnadi; Isabel Hanekamp; Jayne Marie Muoio; Casey Winter; Nicole Hays; James S. Allan; Joren C. Madsen (Scientific Reports)
Abstract The thymus is a rich source of regulatory T cells and plays a role in self-tolerance. Therefore, transplantation of a vascularized donor thymus may facilitate the induction of tolerance in recipients of a cotransplanted heart allograft. To investigate this hypothesis, we developed a new technique to procure the heart and thymus en bloc from juvenile donors and transplant the composite allograft into thymectomized recipients. Thymic function was monitored by serial biopsy and flow cytometry of peripheral blood. Heart-thymus en bloc transplantation resulted in immediate revascularization of the heart and donor thymus with maintenance of normal thymic architecture, even in biopsies taken months after transplantation. Heart-thymus en bloc transplantation requires minimal modification to current heart procurement techniques. Here, we describe the details of the preparation, procurement, transplantation, and postoperative monitoring for this model, with the intention that this technique could be implemented by other investigators to study the effects of heart and thymus cotransplantation. This method could ultimately offer a new approach to tolerance induction in children.